American Sexual Character : Sex, Gender, and National Identity in the Kinsey Reports. - Reumann, Miriam G., 1966- (University of California Press, 2005)
When Alfred Kinsey's massive studies Sexual Behavior in the Human Male and Sexual Behavior in the Human Female appeared in 1948 and 1953, their detailed data spurred an unprecedented public discussion of the nation's sexual practices and ideologies. As they debated what behaviors were normal or average, abnormal or deviant, Cold War Americans also celebrated and scrutinized the state of their nation, relating apparent changes in sexuality to shifts in its political structure, economy, and people. American Sexual Character employs the studies and the myriad responses they evoked to examine nati.